Mercury and cyanide in foods from the Amazônia: Is this a risky diet? (International Seven Journal of Multidisciplinary, 2023)
Mercury and cyanide are present in two important types of food that make up the Amazonian table and both are considered toxic to humans, which can cause various diseases and even lead to death. The objective of this study is to discuss the risks of human exposure to mercury and cyanide through food in the Amazon region. The present study is a narrative review developed with studies from the last 20 years (2003 to 2023) selected in the scientific databases Virtual Health Library, Pubmed and Science direct. The results of the selected studies confirm the presence of Hg in fish and cyanogenic residues in cassava flour. In addition, several studies demonstrate the high toxicity of both substances, and that they can favor several negative changes in fundamental systems for the maintenance of life such as the CNS, hematological and cardiac. We conclude that the chronic diet based on contaminated fish and cassava flour poses a risk to the health of fragile and special populations, since they depend mainly on these foods. However, one cannot fail to mention the cultural and economic importance of fish and flour for this population. Therefore, it deserves to be carefully evaluated.